ANALYSIS OF PRICE AND BRAND IMAGE ON PURCHASING DECISIONS WITH SERVICE AS AN INTERVENING VARIABLE (CASE STUDY OF DIGITAL ALLIANCE AT PT AGRES MEDAN TEKNOLOGI - Dini Irhamna; Slamet Widodo; Husni Muharram Ritonga (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of price and brand image on purchasing decisions, with service quality as an intervening variable, for Digital Alliance products at PT Agres Medan Teknologi. The development of information and communication technology in the digital era has changed consumer behavior and company marketing patterns, especially in the computer hardware industry. Digital Alliance, known for its competitive prices and reliable product performance, faces challenges in maintaining and increasing consumer purchasing decisions. This study uses a quantitative method with a survey approach to 180 consumers. The results show that price and brand image have a positive and significant influence on purchasing decisions, both directly and through service quality, which functions as an intervening variable. Based on these findings, it is recommended that the company strengthen its pricing and brand image strategies and improve service quality to encourage consumer purchasing decisions. This study provides insights for PT Agres Medan Teknologi in designing more effective marketing strategies to increase customer satisfaction and loyalty.